Tooth Wear (Pathological or Physiological) - Zaker, Makan; Nanobashvili, Ketevan (Caucasus Journal of Health Sciences and Public Health, 2020)
Tooth wear can be defined as loss of tooth surface due to attrition, abrasion or erosion. It can mainly be divided into two groups (pathological and physiological). Much factors play a different role in this process such as malocclusion, TMJ problems, unhealthy diet and para-functional movements. Attrition mostly associated with tooth to tooth contact, abrasion in other hand it deals with foreign objects have contact with surface of the tooth such as tooth brush or hard material food. Erosion can be defined as surface loss of the tooth by non-bacteriogenic acid. Erosion is described exclusively as a surface phenomenon, differs from caries in which there is destruction of both the surface and the subsurface areas of the human teeth. Studies showed that dietary acids are considered to be the main cause of erosion. The interconnection between erosion, abrasion and attrition highlight multifactorial process, that create a worn dentition, in individual there is different variation of involvement of every each one of these factor. In some cases the main cause can be erosion and due to that abrasion and attrition take part in this process and cause more severity but also that being said others can be the main cause but generally we cannot differentiate between the absolute causes after the tooth got worn, the goal is here to diagnose, prevent and manage.Many patients and clinicians deal with this process, If not controlled or detected in early stages it can elevate fast and due to its irreversibility treatments are concluded in prosthetic protocols. Main key factor in this process is prevention, monitoring and management. Each individual can has its own version of worn teeth, due to that our methods of approach will be different in every case. We conducted some cases of tooth wear with our associated clinics in Tbilisi, Georgia. We conducted 10 cases of tooth wear that 100% of them has diagnosed with bruxism, from these cases 40% has natural occlusion, 40% straight occlusion, 10% deep occlusion and 10% cross bite. In almost 100% of the cases the severity appears to be at the medium level and in 90% of the cases the tooth wear appeared anteriorly and 10% posterior and the risk factors suggested 60% of the cases have direct connection with malocclusion. As it’s indicated in data that 60% of these cases had malocclusion so this can point out the correlation of the severity with unbalanced occlusion. The main point of this research was to find correlation between all the aspect of tooth wear (attrition, abrasion, erosion) to any para-functional movements, TMJ disorders, bad oral habits, oral disorders and different type of diets for assessing the main reason why this process takes first place. This is a delicate matter so it is better to deal with it at first stages, so we can prevent the prognosis of the wear.